Cosmopolitan Learning, Making Merit, and Reproducing Privilege in Indian Schools. (26th July 2016) - Gilbertson, Amanda
Abstract : Amid growing calls for education to be more globally oriented, scholars have asked how best to educate for global citizenship and what truly cosmopolitan learning looks like. This article draws on ethnographic fieldwork in middle‐class Hyderabad, India to highlight the overlap between the cosmopolitan competencies promoted in schools and uppezr middle‐class cultural capital, and to question whether it is possible to legitimate and institutionalize cosmopolitanism as merit within education systems without furthering class reproduction.